Evaluating anti-MRSA antibiotic stewardship with a focus on trends in consumption and resistance in a tertiary hospital in Alexandria, Egypt from 2019 to 2023 - Ehab Elmongui; Adel Zaki; Amel Elsheredy; Asmaa Abd Elhameed (Archives of Public Health)
Abstract Background The global rise of antimicrobial resistance (AMR) threatens infection treatment. Methicillin-resistant Staphylococcus species (MRSS) are particularly challenging. This study examines the relative consumption of Linezolid (Reserve antibiotic) versus Vancomycin and Teicoplanin (Watch antibiotics) for MRSS, comparing trends with resistance patterns to optimize antibiotic use and combat AMR. Methods This observational retrospective study analyzed trends in the consumption of Vancomycin, Linezolid, and Teicoplanin among all patients admitted to a tertiary hospital in Alexandria, Egypt from January 2019 to December 2023. The study compared these consumption patterns with resistance rates in Staphylococcus spp., including MRSS, from January 2020 to December 2023. Data on antibiotic consumption, expressed as defined daily doses per 1000 patient days (DDD/1000PD), were retrieved from pharmacy records, while resistance data were obtained from the WHONET database. Exploratory data analysis, including time series visualization and linear regression, assessed trends and the impact of COVID-19 on antibiotic use and resistance patterns. Results Linezolid consumption increased significantly (β = 3.72, 95% CI: 0.50 to 6.94, p = 0.027), while Teicoplanin consumption also rose but to a lesser extent (β = 1.81, 95% CI: 1.02 to 2.60, p < 0.001). Vancomycin consumption remained stable (β = -0.31, 95% CI: -0.77 to 0.15, p = 0.184). Overall, Linezolid experienced an increase in usage that was 2.5 times steeper compared to the combined use of Vancomycin and Teicoplanin. The ICU surveillance data indicated that the days of Vancomycin therapy per 1000 patient days decreased significantly (β = -5.02, 95% CI: -6.79 to -3.25, p < 0.001). Methicillin resistance remained high ranging from 47.8 to 85.2%. Throughout the study period, resistance to the three antibiotics was higher than resistance rates reported in other published studies across Egypt while remained stable and comparable between the hospital and ICU. In the hospital, resistance ranged from 4 to 23.7% for Vancomycin, 6.3–28.6% for Linezolid, and 0–41.7% for Teicoplanin. In the ICU, Vancomycin resistance ranged from 5.5 to 34.2%, Linezolid from 11.4 to 41.2%, and Teicoplanin from 7.1 to 38.8%. Conclusions This study underscores the urgent need for antimicrobial stewardship to reduce Linezolid overuse and address persistently high resistance rates against all anti-MRSA antibiotics.